Genetic Parameters and Genetic Progress of Growth Traits in a Landrace Pig Population - Qiaochu YAN; Qing LIN; Xueyan FENG; Zhanqin SU; Xibo WU; Jinglei SI; Zhe ZHANG; Jiaqi LI (Guangdong nongye kexue, 2022)
【Objective】Four genetic parameters including days to 100 kg (DAYS_100), average daily gain (ADG_100), loin muscle area (LMA_100) and average back fat thickness (BFT_100) at 100 kg body weight in a Landrace pig population were estimated, and the correlations between traits as well as genetic and phenotypic progress of the four traits were analyzed, which could provide a basis for the genetic improvement of the target population.【Method】Records of growth traits of Landrace pigs were collected in a core breeding pig farm in Guangxi from 2002 to 2020. A fixed effect analysis on the factors affecting the growth traits of Landrace pigs was conducted by R software. In addition, the genetic parameters of the four traits were estimated with DMU software and a multi-trait animal model. Furthermore, the genetic correlations and phenotypic correlations between these traits, genetic progress and phenotypic progress were evaluated.【Result】The estimated heritability for the four growth traits of Landrace pigs, including DAYS_100, ADG_100, LMA_100 and BFT_100 were 0.399, 0.391, 0.433 and 0.421, respectively, and all of them had medium to high heritability. Both genetic correlation and phenotypic correlation between DAYS_100 and ADG_100 were significantly negative, with correlation coefficient -0.997 and -0.992, respectively. In general, the phenotypic trend of DAYS_100 was rising while the phenotypic trends of ADG_100, LMA_100 and BFT_100 were declining; the genetic trends of ADG_100 and BFT_100 showed an overall upward trend while the trends of DAYS_100 and LMA_100 were generally downward.【Conclusion】The four growth traits of Landrace pigs are medium-high heritability traits, therefore, their genetic progress can be accelerated through direct selection. There is a strong correlation between DAYS_100 and ADG_100. The management of phenotypic measurement of pig farms and the selection of target traits for pig population breeding have an important impact on the performance of growth traits. In addition, the improvements in farm production management and changes in breed structure may influence genetic progress.